1990
DOI: 10.1007/bf00982094
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular hydrocarbons and defensive compounds ofReticulitermes flavipes (Kollar) andR. santonensis (feytaud): Polymorphism and chemotaxonomy

Abstract: Colonies ofReticulitermes flavipes andR. santonensis were collected from the southeastern United States (Georgia) and the southwest of France (Charente-maritime). Defensive compounds and cuticular hydrocarbons were identified by gas chromatography-mass spectrometry and quantified by gas chromatography using an internal standard for each caste and all colonies. These analyses show that although the cuticular hydrocarbons ofR. santonensis in Europe andR. flavipes in Georgia are identical, their relative proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 27 publications
5
74
0
1
Order By: Relevance
“…The 1 H chemical shift axis was referenced to CHCl 3 , assigned to 7.26 ppm Previously Identified Chemicals. Past research (Zalkow et al, 1981;Bagnères et al, 1990;Nelson et al, 2001;Quintana et al, 2003) Statistical Analyses. In all experiments the number and caste of each termite in each dish was counted every five days.…”
Section: Nuclear Magnetic Resonance (Nmr) Analysis Nmr Analyses Werementioning
confidence: 99%
“…The 1 H chemical shift axis was referenced to CHCl 3 , assigned to 7.26 ppm Previously Identified Chemicals. Past research (Zalkow et al, 1981;Bagnères et al, 1990;Nelson et al, 2001;Quintana et al, 2003) Statistical Analyses. In all experiments the number and caste of each termite in each dish was counted every five days.…”
Section: Nuclear Magnetic Resonance (Nmr) Analysis Nmr Analyses Werementioning
confidence: 99%
“…Studies on social insects have shown that subtle quantitative differences in cuticular hydrocarbon profiles can be detected by analyzing chemical data with multivariate statistical methods. By this approach, cuticular hydrocarbon profiles of social insects have been shown to be species-(e.g., Kaib et al, 1991;Page et al, 2002), caste-(e.g., Bagnères et al, 1990;Klochkov et al, 2005), and colony-specific (e.g., Butts et al, 1995;Lorenzi et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Th e cuticular compounds may also play a role in caste regulation similar to primer pheromones LeConte & Hefetz 2008). Th erefore, the chemical signature and its variations depend on a wide range of factors: endog-enous factors, such as endocrine or enzymatic factors and the regulation of transport paths, etc (Lengyel et al 2007;Schal et al 2003;Fan et al 2004), as well as exogenous factors, such as climate and season (Bagnères et al 1990), diet (Liang and Silverman 2000), the presence of predators, etc. Th e predominance of these factors varies between insects (VanderMeer & Morel 1998).…”
mentioning
confidence: 99%